The Success of the Brand Endorsement Campaign on the Tiktok Account Platform @Adinddadh through the Implementation of Business Ethics Strategies in Building Consumer Trust - Sellvy Anggraeni Mihardja; Selvi Azzahra; Suhendi Suhendi (Peneliti.net, 2024)
This study discusses the success of the endorsement campaign on the TikTok platform via the @adinddadh account with a business ethics strategy approach. TikTok as a short video-based platform provides extensive opportunities for creators to promote products, but ethical challenges often arise in the world of endorsements. This research analyzes how the application of business ethics principles, such as transparency, honesty and communication, builds consumer trust and supports campaign success. The method used is a qualitative study with in-depth interviews with creators and literature analysis. The research results show that strategies that focus on transparency and personal engagement with the audience greatly contribute to increasing visibility and consumer trust. This research provides practical insights for content creators and brands to create ethical and effective campaigns